Dental measurement system for UIAM - Lim, Cheh Siang (2011)
Dental is the place would explore and giving treatment or take care human tooth of health. Nowadays, the dental society is very successful.The technology they using are very modern and it bring many advantages to the dentist and patient such as the modern technology can give dentist get the tooth decay data with accurate compare to the traditional method and save the patient time to always come to find dentist.But because the high technology involve the high cost many in the develop country such as Malaysia, still have many dentist are continue using the traditional method and this situation also occur in many university and one of the universities is Universiti Islam Antarabangsa Malaysia(UIAM) dental clinic.Therefore,this system is the supporting system for UIAM dental clinic to computerize the traditional method and used for process the tooth decay image makes it clearer and provides the calibration and measurement to allow the staff and students UIAM measure the tooth decay based on image.